ORGANIZATION AND MANAGEMENT OF INDUSTRIAL LANDS OF THE TERRITORIAL COMMUNITY - Smoliarchuk М.; Kovalyshyn О.; Shpik Н.; Taratula Р. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
Industrial lands play a significant role in shaping Ukraine's GDP, employment, and various other aspects of the economy. However, from an environmental perspective, they are major sources of negative impacts on the environment. According to current Ukrainian legislation, industrial parks can be established and operated within industrial lands and areas designated as industrial zones in settlements. The present study analyzes and substantiates certain aspects of the development of industrial lands, using one of the territorial communities in Lviv region as a case study. A crucial task for further developing these lands is to determine objectives, select strategies, and implement management decisions to ensure effective future use of community territories. A key focus of this research is on the organization of industrial parks, which, under current conditions, could be a viable way to develop industrial areas within territorial communities and serve as a potential source of revenue for local budgets. However, it is important to note that current legislation provides limited guidance on the principles for selecting land plots and the specific mechanisms for allocating such lands for these purposes within the industrial areas of territorial communities. In general practice, the operation and organization of industrial parks involve five main interdependent stages. These include the initial selection of a land plot for establishing an industrial park, the development of a concept, the selection of a managing company and the conclusion of an agreement with it for the operation of the industrial park, and the final stage, which is the creation and registration of the park in the appropriate registry of the respective country. The choice of land plot is critical to achieving effective results in the future operation of an industrial park. The authors propose criteria for selecting potential sites for new industrial zones, focusing on both ecological and economic aspects in the spatial planning of settlements. These criteria should primarily consider local zoning conditions guided by urban planning documentation, including the master plan, detailed plans, and other relevant urban planning conditions of the studied territory. Specifically, factors to consider include the status of the land plot (LP), its location within the city’s industrial zone (LZ), availability of necessary utilities (NU), planning restrictions (PR), presence of transport infrastructure (TI), placement of parking facilities for the project (PP), regulatory setbacks (RS), and the terrain (TR). Establishing industrial parks on industrial lands within our territorial communities, including the Lviv City Territorial Community, while adhering to the proposed design requirements for land plot selection, will achieve several important objectives. These include reducing environmental and social impacts, fostering economic development, enhancing the investment attractiveness of community territories, and more. Industrial parks contribute to the growth of industrial zones in settlements and help achieve sustainable development goals by creating conditions for socially and environmentally responsible industrialization of the selected community territory.